2016
DOI: 10.1177/0271678x16648712
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Regulatory T cells ameliorate intracerebral hemorrhage-induced inflammatory injury by modulating microglia/macrophage polarization through the IL-10/GSK3β/PTEN axis

Abstract: Inflammation mediated by the peripheral infiltration of inflammatory cells plays an important role in intracerebral hemorrhage (ICH) induced secondary injury. Previous studies have indicated that regulatory T lymphocytes (Tregs) might reduce ICH-induced inflammation, but the precise mechanisms that contribute to ICH-induced inflammatory injury remain unclear. Our results show that the number of Tregs in the brain increases after ICH. Inducing Tregs deletion using a CD25 antibody or Foxp3 DTR -mice increased ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
146
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 162 publications
(153 citation statements)
references
References 46 publications
7
146
0
Order By: Relevance
“…In particular, the role of IL-10 and IL-10 signaling in ICH is largely unclear. Although we cannot formally rule out the effect of rosiglitazone on regulatory T cell-derived IL-10 in our study, previous studies from our lab have shown that IL-10 released from regulatory T cell can regulate microglia alternative phenotype (Zhou et al, 2016). When we injected IL-10, a cytokine which has shown to polarize MMΦ toward alternative activation, intraventricularly into the ICH mice, we found a reduction of hematoma volume at day 3 post-ICH.…”
Section: Discussionmentioning
confidence: 87%
“…In particular, the role of IL-10 and IL-10 signaling in ICH is largely unclear. Although we cannot formally rule out the effect of rosiglitazone on regulatory T cell-derived IL-10 in our study, previous studies from our lab have shown that IL-10 released from regulatory T cell can regulate microglia alternative phenotype (Zhou et al, 2016). When we injected IL-10, a cytokine which has shown to polarize MMΦ toward alternative activation, intraventricularly into the ICH mice, we found a reduction of hematoma volume at day 3 post-ICH.…”
Section: Discussionmentioning
confidence: 87%
“…Ten mice from each group were sacrificed for Western blot analysis on day 7 after MCAO as described previously [3133]. Briefly, mice were deeply anesthetized with an i.p.…”
Section: Methodsmentioning
confidence: 99%
“…CD45 is helpful in this scenario because it is more highly expressed in monocytes than in microglia. Thus, CD45 expression levels can be used to separate these two cell types using flow cytometry: CD45 Int CD11b + cells are microglia and CD45 Hi CD11b + cells are macrophages 4547 .…”
Section: Microgliamentioning
confidence: 99%
“…Complement C3a and C5a are thought to be involved in neuro-inflammation 72 , neutrophil recruitment 73 and blood–brain barrier disruption 45 . ICH-induced microglial activation, as assessed by immunoreactivity to an anti-CD11b and anti-CD11c dual-specificity antibody (OX42), was reduced in C3-deficient mice compared with wild-type controls 74 .…”
Section: Microgliamentioning
confidence: 99%